Indigenous knowledge management in the kelabit community in eastern Malaysia: Insights and reflections for contemporary KM design - Alvin Wee, Yeo; Tariq, Zaman; Narayanan, Kulathuramaiyer (IGI Global Publishing, 2013)
Knowledge audits and assessment help organisations to identify the status of knowledge processes and develop strategies to manage their knowledge-based assets. The structure of Indigenous Knowledge Management Systems (IKMS) is different from the organisation's Knowledge Management (KM) systems and mainly based on the tacit and implicit knowledge forms. Hence, the existing organisation's knowledge audit and assessment tools are not addressing the inherent structure of IKMS. The paper addresses this gap and uses a methodological approach for the assessment of Indigenous Knowledge Management (IKM) processes. The approach is tested in the indigenous Kelabit community of Bario in East Malaysia. The methods used for data collection are survey questionnaire and semi-structured interviews. The study finding argues that indigenous communities exercise the processes of storage, leveraging, sharing and applying knowledge. These processes are a combination of the knowledge and the ways in which this knowledge is put into practice in their daily life activities. These processes may be different but not less effective or less efficient in comparison to organisation's KM processes. The study will help Information and Communication Technology (ICT) researchers to better understand the structure of IKMS and then use this understanding for designing the technological solution for IKM